Effects of combined physical and cognitive training on fitness and neuropsychological outcomes in healthy older adults - Desjardins-Crépeau L (Dove Medical Press, 2016)
Laurence Desjardins-Crépeau,1,2 Nicolas Berryman,2,3 Sarah A Fraser,4 Thien Tuong Minh Vu,5,6 Marie-Jeanne Kergoat,2,6 Karen ZH Li,7 Laurent Bosquet,8 Louis Bherer2,7 1Department of Psychology, University of Quebec at Montreal, Montreal, QC, Canada; 2Research Center, Institut universitaire de gériatrie de Montréal, Montreal, QC, Canada; 3Department of Sports Studies, Bishop’s University, Sherbrooke, QC, Canada; 4Interdisciplinary School of Health Sciences, University of Ottawa, Ottawa, ON, Canada; 5Research Center, Centre hospitalier de l’Université de Montréal, Montreal, QC, Canada; 6Faculty of Medicine, Université de Montréal, Montreal, QC, Canada; 7Department of Psychology and PERFORM Centre, Concordia University, Montréal, QC, Canada; 8Faculté des sciences du sport, Université de Poitiers, Poitiers, France Purpose: Physical exercise and cognitive training have been shown to enhance cognition among older adults. However, few studies have looked at the potential synergetic effects of combining physical and cognitive training in a single study. Prior trials on combined training have led to interesting yet equivocal results. The aim of this study was to examine the effects of combined physical and cognitive interventions on physical fitness and neuropsychological performance in healthy older adults.Methods: Seventy-six participants were randomly assigned to one of four training combinations using a 2×2 factorial design. The physical intervention was a mixed aerobic and resistance training program, and the cognitive intervention was a dual-task (DT) training program. Stretching and toning exercises and computer lessons were used as active control conditions. Physical and cognitive measures were collected pre- and postintervention.Results: All groups showed equivalent improvements in measures of functional mobility. The aerobic–strength condition led to larger effect size in lower body strength, independently of cognitive training. All groups showed improved speed of processing and inhibition abilities, but only participants who took part in the DT training, independently of physical training, showed increased task-switching abilities. The level of functional mobility after intervention was significantly associated with task-switching abilities.Conclusion: Combined training did not yield synergetic effects. However, DT training did lead to transfer effects on executive performance in neuropsychological tests. Both aerobic-resistance training and stretching-toning exercises can improve functional mobility in older adults. Keywords: aging, combined intervention, physical performance, cognitive performance, dual task, executive functions